Dr. Anton Korošec v očeh karikatur - Globočnik, Damir (Časopis za zgodovino in narodopisje, 2022)
The first caricatures of Dr Anton Korošec were published by the German newspapers Marburger Zeitung and Deutscher Montag between December 1917 and October 1918. Korošec was the most frequently caricatured Slovenian politician in the first Yugoslav state. From 1924 to 1928, Korošec’s caricatures were regularly published by the political daily Jutro. The caricature of Interior Minister Korošec, published in Jutro after the shooting in the Belgrade Assembly in June 1928, is considered to be the most highprofile Slovenian caricature, as it sparked protests by SLS supporters.
Keywords: caricature; Deutscher Montag; Dr Karel Verstovšek; Janko Omahen; Jutro; Korošec, Anton; Marburger Zeitung; Milko Bambič; Skovir; Slovenska karikatura